Characteristics and prognostic factors of intracranial hemorrhage in children - Made Kardana; Komang Kari; Made Widia (Paediatrica Indonesiana, 2003)
Objective Finding the characteristics and risk factors associatedwith prognosis in children suffering from intracranial hemorrhage.Methods This was a retrospective medical record review of chil-dren (older than 1 month old) admitted with intracranial hemor-rhage to the Department of Child Health the Sanglah Hospital,Denpasar, during the period of January 1998 to December 2000.Prognostic factors were identified by chi-square and multivariateanalysis with significance of p<0.05Results There were 56 patients eligible for the study. Among themwere 35 (63%) males and 21 (27%) females. Forty-three (77%)were less than one year of age, 40 (71%) without history of traumaand the major clinical manifestation was paleness (89%). The mostcommon location was subdural bleeding, 21 patients (38%). Fac-tors associated with prognosis was the bleeding location (p<0.05)Conclusions Intracranial hemorrhage was more common in malesand in infants. The most common clinical manifestation was pale-ness. Bleeding location was associated with prognosis